Evaluasi User Experience Pada Game PUBG MOBILE Menggunakan Metode Cognitive Walkthrough - Revianda Amrullah Akbar; Hanifah Muslimah Az-Zahra; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PUBG MOBILE is a First-Person Shooter and Third-Person Shooter game that was just released on March 19, 2018. This game including to the category of new game on the mobile platform so that it has the potential to have new users. User Experience is very important for the success of a game on the market, especially on the type of application that has been released. The system that are not well designed and not easy to use will make it difficult for users to learn and operate them, so that they will rarely be used. In order to get a good user experience, an evaluation is a necessary. The Cognitive Walkthrough method is a user experience evaluation method when evaluator provide scenario-based assignment and several questions to game users to find problems that interfere with the learning process. This method is suitable for the system that was just released because it can explore the cognitive processes of users when they first use the system. Respondents used in this study were divided into two groups, namely 3 respondents who had never played PUBG MOBILE games and 3 people who often played PUBG MOBILE games and often played games with similar genres. The evaluation results in the PUBG MOBILE game show that many problems occur because the display is difficult to understand (text and icon) on the task when the user learns about weapons in the game. However, problems that arise are problems that won't affect the main functions of the game.